2011
DOI: 10.1097/phm.0b013e31820b140f
|View full text |Cite
|
Sign up to set email alerts
|

A Telerehabilitation Intervention for Persons with Spinal Cord Dysfunction

Abstract: Pressure ulcers and depression are common preventable conditions secondary to a spinal cord dysfunction. However, few successful, low-cost preventive approaches have been identified. We have developed a dynamic automated telephone calling system, termed Care Call, to empower and motivate people with spinal cord dysfunction to improve their skin care, seek treatment for depression, and appropriately use the healthcare system. Herein, we describe the design and development of Care Call, its novel features, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Telerehabilitation has been evaluated widely in literature and was found to be feasible and effective in various neurological conditions including stroke (Chumbler et al, 2012;Johansson and Wild, 2011;Legg and Langhorne, 2004;Perry et al, 2011), Parkinson's disease (Giansanti et al, 2008) and other non-neurological conditions such as musculoskeletal conditions (Russell et al, 2011;Tousignant et al, 2011), injuries (Bendixen et al, 2008;Forducey et al, 2003;Houlihan et al, 2011) and chronic diseases (Steel et al, 2011). A systematic review analysing telerehabilitation therapies in stroke survivors showed positive outcomes, with a reduction in the risk of deterioration, improved ability to perform activities of daily living, reduced costs and duration of rehabilitation (Legg and Langhorne, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Telerehabilitation has been evaluated widely in literature and was found to be feasible and effective in various neurological conditions including stroke (Chumbler et al, 2012;Johansson and Wild, 2011;Legg and Langhorne, 2004;Perry et al, 2011), Parkinson's disease (Giansanti et al, 2008) and other non-neurological conditions such as musculoskeletal conditions (Russell et al, 2011;Tousignant et al, 2011), injuries (Bendixen et al, 2008;Forducey et al, 2003;Houlihan et al, 2011) and chronic diseases (Steel et al, 2011). A systematic review analysing telerehabilitation therapies in stroke survivors showed positive outcomes, with a reduction in the risk of deterioration, improved ability to perform activities of daily living, reduced costs and duration of rehabilitation (Legg and Langhorne, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…[8][9][10] In stroke patients, telerehabilitation helped to improve their ability to do daily works and reduced costs and the duration of rehabilitation programs. 11 Although the effectiveness of telerehabilitation interventions has been investigated in the treatment of stroke, [12][13][14] Parkinson's disease, 15 musculoskeletal disorders, 16,17 injuries and lesions, [18][19][20] and chronic diseases, 21 it is not clear how using this technology is effective compared with using traditional rehabilitation for therapeutic purposes in the elderly. Therefore, the present study aimed to answer the following research question: how effective are telerehabilitation interventions compared with traditional rehabilitation services for therapeutic purposes in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure ulcers have a variety of negative effects on patients with a spinal cord injury, such as decreases in body image, self-esteem, social relationships, and social activities and increases in hospital readmission. Fortunately, preventive self-care behaviors can contribute to decreasing the incidence of pressure ulcers (Houlihan et al, 2011). Therefore, the most important means of preventing or reducing pressure ulcers is to improve and maintain patients' self-care abilities through skin care, positioning, weight shifting, suitable transfer, and control of the diet and weight.…”
Section: Introductionmentioning
confidence: 99%